Characteristics of cannabis cultivation in New Zealand and Israel. Issue 2 (4th June 2018) - Wilkins, Chris; Sznitman, Sharon; Decorte, Tom; Hakkarainen, Pekka; Lenton, Simon
Abstract : Purpose: The purpose of this paper is to explore the characteristics of small-scale cannabis cultivation in New Zealand and Israel. Design/methodology/approach: An online survey of predominantly small-scale cannabis cultivators had previously been conducted in 11 countries in 2012/2013. The same core online survey was subsequently conducted in New Zealand and Israel in 2016/2017, and comparisons made with the original 11 countries. Findings: Only around one third of the New Zealand and Israeli cannabis growers had sold cannabis, and the majority of these did so only to cover the costs of cultivation. The median number of cannabis plants cultivated per crop by the New Zealand and Israeli growers was five and two, respectively. The leading reasons provided for growing cannabis by both the New Zealand and Israeli growers were to provide cannabis for personal use and to share with others. A higher proportion of New Zealand than Israeli growers reported growing cannabis for medicinal reasons. A total of 16 per cent of the New Zealand and 17 per cent of Israeli growers had come into contact with the police due to their cannabis cultivation. The findings suggest small-scale cannabis cultivation in New Zealand and Israel is largely a means of "social supply" of cannabis, and this is consistent with the findings from the original 11 countries. The higher incidence of growing cannabis for medicinal purposes in New Zealand may reflect the limited official access to medical cannabis. Significant minorities of small-scale cannabis growers in both countries had contact with police, putting them at risk of the negative consequences of a criminal conviction. Originality/value: To date, the research into cannabis cultivation has largely consisted of studies of individual countries. However, given the global popularity of cannabis use, and the recent spread of cannabis cultivation to countries that traditionally have not produced cannabis, via utilisation of indoor growing techniques, there is now a strong case for international comparative research. Following the success of the surveys in the original 11 countries, New Zealand and Israeli members of the Global Cannabis Cultivation Research Consortium international collaboration chose to undertake surveys in their own countries in 2016/2017.